2000
DOI: 10.1681/asn.v1161106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Dose Folic Acid Therapy on Hyperhomocysteinemia in Hemodialysis Patients

Abstract: Abstract. Homocysteine is associated with atherosclerosis and enhanced cardiovascular risk. In previous studies, treatment with folic acid up to 15 mg/d failed to correct hyperhomocysteinemia in the majority of end-stage renal disease patients. A dose of 30 or 60 mg of folic acid per day was compared with 15 mg/d in an attempt to normalize hyperhomocysteinemia in 150 hemodialysis patients. In a randomized, double-blind, multicenter study, 144 patients completed the 4-wk treatment period and 121 patients comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Studies have also been performed to assess the effect of the supplementation of vitamin B6, B12, and folates on homocysteine levels in CKD patients. A study in hemodialysis patients found no improvement in homocysteine levels after a 4-week supplementation of different dosages of folic acid [ 161 ]. Similarly, Wrone et al noted no benefit of folates on cardiovascular event incidence in end-stage renal disease patients [ 162 ].…”
Section: Proteinsmentioning
confidence: 99%
“…Studies have also been performed to assess the effect of the supplementation of vitamin B6, B12, and folates on homocysteine levels in CKD patients. A study in hemodialysis patients found no improvement in homocysteine levels after a 4-week supplementation of different dosages of folic acid [ 161 ]. Similarly, Wrone et al noted no benefit of folates on cardiovascular event incidence in end-stage renal disease patients [ 162 ].…”
Section: Proteinsmentioning
confidence: 99%
“…However, since Hcy muscle inflow is high (Fiona et al, 2009), a defective Hcy transport in muscle in uremia cannot be ruled out from our study. In most normal subjects, a folate dose of 400 to 600 μg produces a prompt fall of 20% to 30% in total plasma Hcy concentrations; in contrast, patients with ESRD are more resistant to this Hcy-lowering action of folic acid and even the use of pharmacological doses of folic acid or reduced folates does not normalize completely circulating Hcy levels (Ducloux et al, 2002;Massy, 2003;Sunder-Plassmann et al, 2000). More commonly occurring vitamin deficiencies in maintenance dialysis patients include those for vitamin C, folate and pyridoxine .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the C677T homozygous polymorphism (TT) of the MTHFR enzyme slows down the enzyme activity, thus the activity of the remethylation cycle, and is associated with significantly higher homocysteine levels [ 8 ]. It has been shown that the A1298C polymorphism of the MTHFR enzyme also affects total homocysteine concentrations and is a risk factor for neural tube defects [ 9 ].…”
Section: Discussionmentioning
confidence: 99%